MULTIFACTOR AUTHENTICATION FOR ONLINE SHOPPING SYSTEM - Muhammad Syazwan Nadzmi Bin Mohd Salwazi; Amna Binti Saad (Journal of Computing Technologies and Creative Content, 2023)
In this project, a multifactor authentication system was integrated with an online store. Digital and computer security are now crucial for safeguarding user data. One threat is shoulder surfing [10], in which a criminal can steal a password by watching directly or by videotaping the authentication process. There are several methods for this authentication, with the multifactor authentication method being the most common and simple. Therefore, a novel strategy is proposed to address this issue, namely the development of multiple layers of system security through the use of multifactor authentications. Text, colour, and graphical representations are the three types of multifactor authentication that are used. At the conclusion of this project, an online shopping system is created to evaluate the effectiveness of the algorithm.